2013
DOI: 10.1039/c3ra41257a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Co2P2O7 nanorods as a promising pseudocapacitive material towards high-performance electrochemical capacitors

Abstract: In the present work, we developed an efficient one-step template-free strategy to fabricate intriguing onedimensional (1D) Co 2 P 2 O 7 nanorods (NRs) at room temperature, and utilized the unique monoclinic Co 2 P 2 O 7 NRs as an excellent electrode material for high-performance pseudocapacitors using 3 M KOH as an electrolyte. Strikingly, the as-synthesized 1D Co 2 P 2 O 7 NR electrode delivered a specific capacitance (SC) of 483 F g À1 at 1 A g À1 , and even at 402 F g À1 a high current loading of 10 A g À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…Khan et al reported a maximum capacitance of 580 F g −1 (1 A g −1 ) for Co 2 P 2 O 7 ‐based electrode in a redox‐active electrolyte. In another work, Hou et al synthesized one‐dimensional (1D) Co 2 P 2 O 7 nanorods (NRs) at room temperature and obtained a maximum specific capacitance of 483 F g −1 at 1 A g −1 . Despite these achievements, metal pyrophosphates have a limited electrochemical performance specifically in terms of the low working potential window, specific capacitance, and cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al reported a maximum capacitance of 580 F g −1 (1 A g −1 ) for Co 2 P 2 O 7 ‐based electrode in a redox‐active electrolyte. In another work, Hou et al synthesized one‐dimensional (1D) Co 2 P 2 O 7 nanorods (NRs) at room temperature and obtained a maximum specific capacitance of 483 F g −1 at 1 A g −1 . Despite these achievements, metal pyrophosphates have a limited electrochemical performance specifically in terms of the low working potential window, specific capacitance, and cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nickel based materials (NiO, Ni(OH) 2 , NiCo 2 O 4 , NiFe 2 O 4 , NiMoO 4 , Ni 3 (PO4) 2 and Ni 2 P 2 O 7 ., etc) have been considered as fascinating battery electrode materials for hybrid capacitors due to low cost, high capacitance and environment friendly. [12][13][14][15][16][17][18][19][20][21][22] Though pyrophosphate materials (Co 2 P 2 O 7 , Mn 2 P 2 O 7 and Ni 2 P 2 O 7 ) have captivated the attention from researcher worldwide, [22][23][24][25] however, there is only one recent study on nickel pyrophosphate (Ni 2 P 2 O 7 ) reported by Wei et al They synthesized hexagonal tablets of sodium doped Ni 2 P 2 O 7 by hydrothermal method which delivers its maximum capacitance 557.7 F g -1 at 1.2 A g -1 . 22 It is worth to mention, though they made high surface area hexagonal tablet but still the capacitance value is low.…”
Section: Introductionmentioning
confidence: 99%
“…Other 1D nanostructures, such as NRs, NTs, and NBs, have been extensively studied for their applications in supercapacitors . The CoP NRs (Figure a ) are prepared by simply thermal decomposition of the cobalt acetylacetonate in oleylamine system with triphenylphosphine as phosphorus source, and display a SC of 284 F g −1 (198.8 C g −1 ) along with good rate capability .…”
Section: The Applications Of 1d Nanostructured Pcms In Supercapacitorsmentioning
confidence: 99%
“…Hou et al. have developed an efficient template‐free strategy for synthesizing monoclinic Co 2 P 2 O 7 NRs towards high‐performance supercapacitors, and propose the possible charge storage mechanisms of the Co 2 P 2 O 7 NRs in KOH electrolyte . Yan and co‐workers reported the oxidation‐etching preparation of MnO 2 NTs (Figure b) .…”
Section: The Applications Of 1d Nanostructured Pcms In Supercapacitorsmentioning
confidence: 99%